Pendampingan Penyusunan Perangkat Pembelajaran Inovatif bagi Guru Matematika SMP dan MTs di Kecamatan Labuapi Lombok Barat melalui Kegiatan LSLC - Sripatmi Sripatmi; Nyoman Sridana; Arjudin Arjudin; Nourma Pramestie Wulandari; Ulfa Lu’luilmaknun (Rengganis Jurnal Pengabdian Masyarakat, 2022)
Learning is an interaction process of students with teachers and the learning sources in a learning environment. Therefore, the planning is needed to ensure the learning process run properly, consisting of 3 stages namely designing/composing, the learning implementation, and the evaluation and reflection. Those three stages can be improved by the Lesson Study for Learning Community (LSLC) activity. Based on the discussion with some principals and mathematics teachers of SMP and MTs in Labuapi, West Lombok, it was revealed that: i) mathematics is a subject which attracts less interest of junior high school students in Labuapi, ii) some mathematics teachers still found difficulties in composing an innovative learning devices which can guide students to find out the concepts, principles, and the solutions from the mathematics problems, and also they still have difficulties in designing one-page learning scenario which can actively involve students in an enjoyable learning process. To solve the problems, the mentoring activity in composing the learning through the LSLC activity is urgently needed. The activity was carried out by utilizing some methods, namely: speech, question and answer, discussion, and conducted mentoring activity when mathematics teachers discussed about the composing of LSLC based learning devices. From the mentoring activity conducted in 3 and 10 until 13 of September 2022, it was concluded that the mentoring activity was able to improve some aspects as follows: i) the understanding of mathematics teachers of SMPN/MTs in Labuapi, West Lombok in composing an innovative learning device, consisting of lesson plan or lesson design, learning materials, learning media, and assessment instrument; ii) the skill of mathematics teachers in the level of junior high schools in Labuapi, West Lombok in designing the learning devices as set in the curriculum of 2013; iii) the collegiality among teachers of SMPN and MTs in Labuapi, West Lombok in teaching and fulfilling students’ right from the sharing of experiences through the LSLC activity.